Penggunaan media kartu kata untuk meningkatkan keterampilan membaca siswa kelas II SD materi dongeng - Happy Aprilia Sanday; Reza Rachmadtullah; Feny Rita Fiantika (Nautical : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
This research is motivated by the current pandemic conditions which require students to study from home. There are several factors that make students less attractive to study, namely, the students' lack of interest in learning which is getting higher and teaching materials that are less interesting in learning. This research uses the type of classroom action research or commonly known as the Kemmis and Mc. Taggart. The research was conducted in two cycles. The subjects of this study were second grade students of SDN Margorejo 1/403, totaling 29 students. Data collection techniques used are tests and observations. Meanwhile, the data collection instrument used a reading test using word cards and observation sheets. Data analysis technique using percentage. student learning outcomes, namely the average value of the class in the pre-cycle of 66.37 then in the first cycle to 72.24 and the second cycle to 80.51. The number of students who achieved KKM > 75 in the pre-cycle there were 11 students in the first cycle there were 20 students and in the second cycle there were 27 students. The percentage of completeness in the pre-cycle is 38%, the first cycle is 69% and the second cycle is 93.1%. So that in the second cycle, more than 80% of students reached the KKM > 75 criteria.